ANALISIS BAURAN PEMASARAN (MARKETING MIX) PADA PT. TAKAFUR KELUARGA CABANG PALEMBANG - Andrie Fernanda; Choiriyah Choiriyah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2018)
This study aims to determine the Marketing Mix and to determine the obstacles in implementing the Marketing Mix at P.T Takaful Keluarga Branch of Palembang. In this paper, the author uses field research with qualitative data types using one data source, namely primary data. The technique of data collection was carried out by interviewing and documentation that could answer the existing problems, and so the data were analyzed descriptively and qualitatively. From the results of this study that the Marketing Mix or 7 P which consists of: Product, Price, Place, Promotio, Process, Physical Environment used by PT. The Palembang Branch of the Takaful Family is in accordance with the existing producers, while for application in the field there are several obstacles that arise in terms of People and Promotion, so this Marketing Mix is not going well.